2002
DOI: 10.1007/s00431-002-0977-x
|View full text |Cite
|
Sign up to set email alerts
|

Cleidocranial dysplasia with decreased bone density and biochemical findings of hypophosphatasia

Abstract: we suggest that the observed metabolic alterations are secondary to the RUNX2 gene mutation affecting early bone maturation and turnover. This is the first description of biochemical findings of hypophosphatasia in patients with cleidocranial dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
4
14
0
4
Order By: Relevance
“…Studies to identify the mechanisms by which RUNX2 and TNSALP interact will provide important molecular evidence to support our clinical hypothesis. In the interim, recognition of the hypophosphatasia phenocopy in some CCD patients [9] should help prevent misdiagnosis and clarify the varying natural history of this disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Studies to identify the mechanisms by which RUNX2 and TNSALP interact will provide important molecular evidence to support our clinical hypothesis. In the interim, recognition of the hypophosphatasia phenocopy in some CCD patients [9] should help prevent misdiagnosis and clarify the varying natural history of this disorder.…”
Section: Discussionmentioning
confidence: 98%
“…(12) Abnormalities in RUNX2 function can lead to cleidocranial dysplasia (CCD), in which there is defective ossification of the cranial bones with large fontanels and delayed closing of the sutures with complete or partial absence of the clavicles. (13)(14)(15)(16)(17)(18)(19) Mice with homozygous mutations in RUNX2 cannot survive after birth owing to breathing defects caused by the absence of ossification of the ribs. (20,21) The functions of RUNX2 and SOX9 are controlled by transcriptional and posttranscriptional regulation, including ubiquitination, phosphorylation, and acetylation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although the patient has the complete heterozygous deletion of Runx2 , master gene of OB differentiation, we found that serum markers of OB activity as bone alkaline phosphatase and osteocalcin are in the control range. According to our results, other authors demonstrated that alkaline phosphatase function is disturbed in only serious cases, in which CCD is also associated to hypophosphatasia 32, 33. The major limitation of our study is that the results refer to a single patient, seeing as the CCD is a rare skeletal dysplasia.…”
Section: Discussionmentioning
confidence: 55%